Reliance Industries launches Mission Vaccination - Reliance Industries Limited (2022)
On May 1, Reliance rolls out its free COVID-19 vaccination programme across locations for all employees, off-roll workforce staff, and eligible family members. Reliance administers over 12 lakh COVID-19 vaccine doses free to employees, off-roll workforce staff, and family members across India. Reliance Foundation extends the vaccine programme to marginalised communities.